Geological Structure and Possible Mineralized Zones in Ikungi – Manyoni Area, Tanzania: Delineated from High-resolution Aeromagnetic Data - Pius, Raymond K.; Msabi, Michael M. (Tanzania Journal of Science, 2024)
Understanding geological structures is important in mineral exploration. Delineating subsurface geological structures, structural intersections, and complexities of potential geological settings for the formation of hydrothermal mineral deposits, such as gold requires using magnetic data, particularly, high-resolution aeromagnetic data. To define possible targets for mineral exploration, this study used linear detection and the Centre for Exploration Targeting (CET) techniques on high-resolution aeromagnetic data for structural delineation and interpretation. The study's conclusions indicate that the majority of geological features, such as faults, shears, fault intersections, and fracture systems, trend NE-SW, N-S, and occasionally NW-SE. These structures create potentially large areas that have a strong chance of becoming mineralized. The CET grid analysis technique defined mineralized zones, particularly the structural intersections which are potential targets in mineral exploration. The effectiveness of the CET technique in mineral prospecting was demonstrated by the correlation between the results and existing mineral occurrences (such as Shanta Gold Mine, abandoned pits, and the operating pits of small-scale miners in Muhintiri). Based on the findings reported herein, any sites that share characteristics with those that have demonstrated gold mineralization should be prioritized for ground follow-up.